Effect of Multiplication and Absorption Layers Width on Avalanche Multiplication Gain in InGaAs/InP Avalanche Photodiode - Khamis, Mahdi All; Rashid, W. Emilin; Ker, Pin Jern; Lau, K. Y. (International Journal of Engineering and Technology, 2018)
The separate absorption, grading, charge, and multiplication (SAGCM) InGaAs/InP avalanche photodiodes (ADPs) are widely used in long distance, high bit rate optical communication system due to their high performance and response to optical fiber wavelength spectrum. In this work, the effect of multiplication layer width (MLW) and absorption layer width (ALW) on APD performance is studied and investigated. Silvaco TCAD software is used as simulation tools to simulate a precise model of InGaAs/InP APD and analyze its, performance under an illuminated condition. As such, three different ALW with various MLW has been simulated while the structure values and material parameters are kept constant. It was found that in the APD with smaller MLW, the distance between the punch-through voltage and the breakdown voltage can be maximized. Therefore, the operation region of APD will be extended. In addition, the multiplication gain is obtained from the photocurrent and primary current by taking the APD collection efficiency effect under the consideration.